Choroidal imaging: A review - Chhablani, Jay (Elsevier, 2014)
Being the most vascular tissue of the eye, importance of the choroid has been very well established in various retinal and chorio-retinal diseases. Understanding of the choroidal structures has improved significantly since the evolution of enhanced depth imaging. Quantitative assessment of choroidal measurements has been found to be reproducible using different devices. This review article describes factors affecting choroidal thickness and choroidal changes in several diseases and reports its clinical importance. Evaluation of choroid would provide insight into the pathogenesis, treatment planning and follow up in chorioretinal diseases.